A modern approach of Khayr al-Din al-Tunisi to the program of reform - Abdul Rahim, Adibah (Hamdard Foundation Press, Pakistan, 2008)
This paper attempts at introducing Khayr al-din al-Tunisi as one of the Arab political thinkers in the nineteenth century. The discussion focuses on his modern approach of social institutions and law, particularly through his famous work Aqwam al-Masalik fi al-MaÑrifat al-Mamalik. This book was written in terms of the milieu in 1860’s, which represented roughly the mid- period of the tanzimat era in the central Ottoman Empire. It was an age, which brought a major European political and ideological challenge to Islamic society. The Islamic society also had lived through many military challenges coming from outside. By the 1860’s, Tunisia had experienced modernization efforts of Ahmad Bey (1837-1855). During this time, Tunisia had proclaimed and suspended a constitution patterned closely on European liberal constitution. The political program which Khayr al-din wrote in 1867 was conceived in full knowledge of this immediate past. In general, study of the impact of the West has concentrated on the two areas of Turkey and Egypt. This is justified since the Egypt of Muhammad ÑAli and his successors and the Ottoman Empire were the two great centers of Muslim political strength in the nineteenth century. Besides Egypt, however, Tunisia was the only other example of an autonomous Muslim state, which was at the same time within the general Ottoman framework. Egypt, Tunisia, and Ottoman Empire actually were facing the political and ideological threat coming from the West. In all three states systems, there were attempts at westernizing beginning with the army. All three received different foreign technical advisers. They were also made gestures toward Western forms of constitution and civil rights. Due to these similarities, the problems discussed by Khayr al-din in his Aqwam al-Masalik and the solution he proposed were pertinent also to Egypt and the Ottoman Empire. Indeed, the similarities to conditions in the Ottoman Empire were even emphasized by Khayr al-din himself. His effort was seen as a political program for Tunisia justified in terms of evidence and arguments valid for all parts of the Ottoman world. Aqwam al- Masalik, therefore, is an important source for Tunisian history in nineteenth century, but at the same time it can help to clarify comparable situation in Egypt and the Ottoman Empire.